Ciencia abierta en universidades latinoamericanas: avances y desafíos institucionales - Dra. Dina Makarova Siegmund-López (Revista Científica Multidisciplinaria Jetypeka, 2025)
Open science has emerged as a transformative paradigm that redefines how scientific knowledge is produced, disseminated, and evaluated. This article analyzes the current state of open science in Latin American universities, identifying key practices, regulatory frameworks, and structural barriers to its consolidation. Based on a qualitative documentary analysis, the study systematizes policies, case studies, and academic literature. Findings reveal significant progress in open access publishing, but also highlight persistent limitations in technological infrastructure, academic evaluation, and institutional culture. A critical perspective from educational management and context-based pedagogy is adopted to explore the transformative potential of open science in Latin America. Strategic recommendations and future research directions are provided to promote its sustainable implementation.
Open science in Latin American universities: institutional advances and challenges
Keywords: open science, higher education, Latin America, open access, academic evaluation, educational management.